Imaging of cerebral venous thrombosis. Issue 4 (April 2020) - Ghoneim, A.; Straiton, J.; Pollard, C.; Macdonald, K.; Jampana, R.
Abstract : The incidence of cerebral venous thrombosis (CVT) is increasing due to the widespread use of computed tomography (CT) and magnetic resonance imaging (MRI) for investigating patients with acute headaches and new onset of seizures. Alternatively referred to as cerebral venous sinus thrombosis (CVST) or dural venous sinus thrombosis (DVST), the terms encompass a broad spectrum of neurological pathologies. These include dural venous sinus thrombosis, cortical vein thrombosis, cavernous sinus thrombosis, venous infarction/haemorrhage, and the rare sequelae of intracranial hypertension or dural arteriovenous fistula. Timely and accurate diagnosis is critical; most patients are young adults and up to 15% will die in the acute phase of the condition. Imaging diagnosis using unenhanced CT or CT venography (CTV) can be readily achieved by the general radiologist. MRI or MRI venography (MRV) are powerful techniques, provided the radiologist is aware of critical diagnostic pitfalls. In selected cases, cerebral digital subtraction angiography (DSA) can facilitate both diagnosis and anticoagulant/transcatheter thrombolytic therapy improving clinical outcome. This article will outline the condition, highlighting cerebral venous anatomy, diagnostic techniques, and pitfalls pertinent to all practising radiologists.